A Survey of Antibiotic-Resistant Microorganisms in Hospital Sink Drains. (October 2020) - Franco, Lauren; Ganim, Christine; Tanner, Windy
Abstract : Background: Handwashing sinks in healthcare environments are reservoirs for healthcare pathogens and antibiotic-resistant microorganisms (ARO). We investigated the distribution of HCP and ARO within and among handwashing sinks in healthcare settings. To do this, we determined the differences in the number of ARO between samples within a sink (biofilm vs planktonic samples), between sink types (healthcare worker [HCW] vs patient room sinks), and between hospitals in the same city. Methods: Tap water, sink surface, drain cover, tail pipe, p-trap water and p-trap samples were collected from 2 patient room sinks and 2 HCW sinks over 11 months in 2 acute-care hospitals. Suspected pathogens were isolated from selective media (Pseudosel, Chromagar KPC, and MacConkey with 2 mg/L cefotaxime) and identified via MALDI-ToF. Isolates confirmed to be healthcare pathogens were characterized via disk diffusion to determine their antibiotic susceptibility according to CLSI guidelines. Isolates not susceptible to carbapenems (meropenem or ertapenem) were tested further via the modified carbapenem inactivation method to detect carbapenemase production. Results: Pseudomonas aeruginosa and Enterobacteriaceae ( Enterobacter spp, Klebsiella spp, and Citrobacter spp) were the most frequently isolated pathogens. Among these isolates (195 P. aeruginosa and 42 Enterobacteriaceae isolates), 28.5% of P. aeruginosa and 85.7% of Enterobacteriaceae were nonsusceptible to 1 or more of the antibiotics tested. Of the isolates that were nonsusceptible to a carbapenem (46 of 237; 19%), none displayed phenotypic carbapenemase production. Other mechanisms of resistance have not been confirmed. There was no significant difference in the percentage of nonsusceptible HCP isolated from biofilm samples (from p-trap and tail pipe) compared to planktonic (p-trap water) samples ( P > .05 for P. aeruginosa and Enterobacteriaceae). A greater percentage of resistant or intermediate isolates was recovered from patient room sinks than from HCW sinks ( P < .05) for both P. aeruginosa and Enterobacteriaceae isolates (76.4 vs 32.9% for Enterobacteriaceae, 25.6 vs 0.3% for P. aeruginosa ). We detected no significant difference in percentage of nonsusceptible isolates between the 2 hospitals sampled ( P > .05). Conclusions: This survey of healthcare sinks supports previous work citing that they are reservoirs for HCP and ARO. This work further examines the distribution of HCP and ARO within and among sinks in these environments. Our findings thus far in the 2 hospitals studied reveal a higher percentage of ARO in patient sinks than in HCW sinks. This finding may suggest a higher input of ARO from patient use or greater selective pressure in patient room sinks. Disclosures: None Funding: Lauren Franco, Centers for Disease Control and Prevention